ACCESSIBILITY STANDARD OF PRIMARY SCHOOL WITHIN KANKE LOCAL GOVERNMENT AREA OF PLATEAU STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
The relevance of site planning in journey to and from school revolves around accessibility. Rural residential location is a function of accessibility and distance. Town and school planners try to ensure pupils travel distance do not affect their academic performance, hence it’s stipulated 32.00>26.30 as school attendance is a function of distance from pupil home. PCC test of distance reliability with 95% test of confidence; 0.05 revealed H2; School attendance is affected by distance. Commendation is school planners should comply with stipulated accessibility standard, the establishment of school clinic.
Keywords: Accessibility, Site planning, Residential location and Travel Hazard